Kajian Literatur Media Pembelajaran Interaktif Berbasis Artificial Intelligence dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Arina Mana Sikana; Diah Ayu Pramita; Isna Mutiarani; Nisa Ayu Falentin; Vivi Rulviana (Prosiding Konferensi Ilmiah Dasar, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed educational practices, particularly in the development of innovative, interactive, and adaptive learning media. This study aims to examine the role of AI-based interactive learning media in enhancing elementary school students' learning motivation. The research employed a qualitative approach using a library research method. Secondary data were collected from national and international journal articles, books, conference proceedings, and official documents published between 2019 and 2025 and accessed through Google Scholar. The data were analyzed using content analysis, including literature collection, article selection, thematic classification, interpretation of previous research findings, and conclusion drawing. The findings indicate that AI-based interactive learning media can enhance students' learning motivation by providing engaging, interactive, personalized, and adaptive learning experiences. AI also supports teachers in developing learning media more effectively through the creation of instructional materials, educational illustrations, learning videos, interactive quizzes, and automated feedback. However, the implementation of AI in elementary education still faces several challenges, including teachers' digital competencies, technological infrastructure, and ethical issues related to AI utilization. Therefore, AI should be implemented responsibly while maintaining the teacher's central role as a facilitator of learning. This study provides a comprehensive overview of the potential of AI-based interactive learning media as an educational innovation to improve elementary school students' learning motivation